(3GdaQb Hjf GdMdGd hGdMQGe aj GdZfGAs - (3CHh GdQHjY SdjeGf Hf eMeO Hf YHO Gddg Hf ESeGYjd GdTQja GdYdhj, Gdehdj SdjeGf,J (B1238 (3g` s
(3ChdgG (B:s
(3hHYO deG QCjJ GdcKjQ ef GdYdhe Hd GdabgGA GdCYdGe jMVQ eLGdS GdZfGA HGdYhO hGdQHGH s
(3BNQgG (B:s
(3R cja jDef Ydi gPg GdeSFdI hZjQgG heG cfG dfgJOi dhdG Cf gOjfG Gddg s
(3HChdg agQSJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B133s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdehSjbi hGdZfGAs